PENGARUH INFLASI, JUMLAH PENDUDUK, DAN PENGELUARAN PEMERINTAH TERHADAP GDP JEPANG TAHUN 2011-2020 - Randy Admi (Oikos Nomos: Jurnal Kajian Ekonomi dan Bisnis, 2022)
This study aims to analyze the effect of inflation, population, and government expenditures on Japan's GDP in 2011-2020. The type of research used is quantitative descriptive research with secondary data obtained from the World Bank. The data analysis technique used in this study is multiple regression analysis with the help of E-Views 10 software. The results of the study found that inflation has no significant effect on GDP, population has a negative and significant effect on GDP, and government expenditures has a negative effect on GDP.